SISTEM PENDUKUNG KEPUTUSAN PENJURUSAN SISWA BERBASIS PHP MYSQL (Studi Kasus : SMA ADABIAH PADANG) - Eva Yulianti; Fikri Kurniawan (ITP Press, 2013)
Direction performed in high school performed in class X at SMA Adabiah Padang has done with the calculation of the value of math, science, social studies, IQ tests, and interests of students, the premises still computation performed manually by using media such as the record books data must be very economical and also much time in calculating the results of the placement of students class X. Applications are made at this final direction to help high school students of class X in Adabiah Padang. In determining the placement of students used methods of AHP (Analytical Hierarchy Process) as a tool to determine the placement of students with multiple categories of comparison are: math, science value, the value of IPS, IQ tests, student interest and parental support. Web-based application is created using PHP as the programming language and MySQL as the data storage. The process used in determining the placement of students using the application that created it easier and faster to update the data from assessments to support placement of students and resource usage can minimal books and papers used in the old system and certainly more economical, because the system uses which has been computerized